SALT TOLERANCE OF TURFGRASS Puccinellia dirtans: II. IONIC INTERACTION IN THE ROOTS - Didy Sopandie; Masumi Moritsugu; T. Kawasaki (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
In this study, multi-compartment transport boxes were used to determine the mobility of ions in the execised roots. For measuring Na uptake, the concentrations of 1, 50 and 150 mM NaCI were used in the external medium, whilst Ca were 0 and 2. 0 mM. The uptake of K was measured from 1.0 mM KCI in the presence of Na (0.50 and 150 mM) and Ca (0.50 and 2.0 mM). In the present study, 22 Na and 86 Rb were used to label Na and K in the external medium, respectively. Addition of Ca inhibited Na uptake in the roots exposed to 1.0 mM and 50 mM NaCI, thought Ca was relatively less effective in 150 mM. High concentrations of NaCI brought about the reduction of K uptake. Calcium, however, did not show any importance in recovering the uptake of K from the adverse effect of Na when the roots were exposed 10 50 mM NaCI, thought stimulating effect of Ca was observed at 150 mM NaCI. The results revealed that the pattern of ionic interactions in Puccinellia distans differs much with that generally found in most of halophyte plants.